Integrasi Pembiasaan, Hafalan dan Praktik Mufradat untuk Membangun Afeksi Positif pada Pembelajaran Bahasa Arab Tingkat Sekolah Menengah Atas - Zaidaan, Muhammad; Shafa Aurel Mardhotillah; Nadhif Athallah Putra Fadliardi; Raswan, Raswan (Journal of Arabic Language Studies and Teaching, 2025)
Student motivation for learning Arabic in secondary school appeared low, indicating a discrepancy between the learning objectives of developing communication skills and the teaching methods, which still focused on memorisation. This study aimed to evaluate the effectiveness of combining habituation, memorisation, and vocabulary understanding in shaping positive attitudes among students. The study used a descriptive, qualitative method, observing classes and interviewing Arabic teachers. The results showed that familiarisation through vocabulary media helped students become accustomed to the language, structured memorisation improved memory, and communication exercises provided confidence and a positive attitude. By combining these three strategies, Arabic language learning became more balanced in developing cognitive, affective, and psychomotor aspects. This study made theoretical contributions to the development of an integrated Arabic language learning model and offered practical suggestions for educators to create a more contextual and communicative learning environment.